Retention of pit and fissure sealant versus flowable composite: An in vivo one-year comparative evaluation - Charanjeet Singh; Kamalpreet Kaur; Kavisha Kapoor (Wolters Kluwer Medknow Publications, 2019)
Introduction: Pits and fissures are extremely vulnerable to the development of caries. Resin-based materials for sealing pits and fissures (pit and fissure sealants and flowable composites) are helpful in caries control by physical barrier formation, which prevents metabolic exchange between fissure microorganisms and oral environment. Retention is one of the most important prerequisites for pit and fissure sealants. Debris and pellicle might not be removed by conventional prophylaxis and etching; therefore, air abrasion (AB) for fissure preparation has been advocated for sealant retention. This in vivo study was aimed to compare the retention of resin-based pit and fissure sealant to flowable resin composition occlusal pits and fissures of all first permanent molars with and without air-abrasion over a 12-month follow-up. Materials and Methods: A randomized controlled clinical trial was done after obtaining ethical committee approval and informed and written consent. Thirty children with the age of 6-9 years, with all four caries-free first permanent molars without any hypoplasia/fracture but with pits and fissures prone to caries were included in this study. The four first molars were divided into the following four groups: Group A (tooth 16; sealant + AB), B (tooth 46; composite + AB), C (tooth 36; sealant), and D (tooth 26; composite). Assessments were made at 3, 6, 9, and 12 months for partial or total loss of sealant and caries according to Modified Simonsen's Criteria. Results and Conclusions: Flowable composite was relatively better retained than sealant at 12 months' follow-up although results were statistically insignificant. AB followed by acid etching brought superior retention than acid etching. Mandibular teeth have shown relatively superior retention. Future studies should aim at investigating better techniques and materials for sealing pit and fissures.